Online purchase intentions among UUM postgraduate students - Sulaiman, Yaty (2017)
Purpose - This study aims to identify and examine the factors that influence online purchase intentions among postgraduate students in context of Malaysia. Seven dimensions were used in this study consisting of product, price, promotion, product risk, delivery risk, privacy risk and financial risk. Online market is one of the industries that are currently developing and have many potentials to become one of the best market in the world. Many entrepreneurs have started to move from plain brick and mortar business to adopt both physical and online shops to set up their business and attract customers. There are also some entrepreneurs that only focus on online commerce and only set up online shops to perform their business.Due to this advantage, online shopping is not perceived as a complement market by some and are even perceived as a major threat by company that mainly engage in traditional based business.Stores may also become more appealing and convenient in terms of time, place, and purchasing modalities, and hedonic value (Hao, 2013). Students are one of the prospects customers that have interest and skills to patronage and use online shopping skillfully. This study results reveals that the highest dimensions to affect online purchase intentions are products factors.Meanwhile delivery and financial risk are revealed to have no significant relationship with online purchase intentions among postgraduate students.Methodology - This study was conducted used quantitative method. Data were collected in UUM and 500 questionnaires were distributed and 394 of them were returned and valid to be used as the sample for the study. Findings - According to Table 1, among Product, Price, Promotion, Product Risk, Delivery Risk, Privacy Risk and Financial Risk, only Product, Price, Promotion, Product Risk and Privacy Risk are able to significantly influence online purchase intention.A variable is able to uniquely influence the dependable variable if the significant (p-value) is below 0.05. So, among all the variables used in this study only Product (0.000), Price (0.005), Promotion (0.006), Product Risk (0.009) and Privacy Risk (0.048) are able to significantly influence online purchase intention. Meanwhile delivery and financial risk are not significant to online purchase intention.